Implementasi Nilai Islam melalui Seni dan Budaya dalam Pendidikan Agama Islam - Nabila Khoirunnisa; Pipih Muflihah; Ratna Dzilla Pebriani; Salman Faris; Abdul Azis (Jurnal Budi Pekerti Agama Islam, 2025)
This study explores the use of art and cultural practices as a means to instill Islamic values in the learning process of Islamic Religious Education. The background of this research arises from the challenges faced by Islamic education in the era of globalization, particularly the declining interest of students in Islamic-oriented activities and the strong influence of popular culture. Using a descriptive qualitative approach by reviewing relevant literature, the study finds that various forms of Islamic art such as nasheed, hadrah, calligraphy, and Islamic-themed drama can help students understand and appreciate religious values in a more engaging and meaningful way. These artistic activities serve as a bridge between Islamic teachings and everyday life, allowing values such as good character, piety, and love for the Qur’an to be internalized more effectively. However, the implementation still encounters several obstacles, including limited teacher competence and insufficient curriculum support. The study concludes that strengthening collaboration with the community, utilizing digital technology, and developing extracurricular programs are important steps to reinforce the application of Islamic values through art and cultural approaches within educational settings.